Citizen science reveals the population structure and seasonal presence of whale sharks in the Gulf of Thailand. Issue 3 (29th June 2022) - Magson, Kirsty; Monacella, Emily; Scott, Chad; Buffat, Noémie; Arunrugstichai, Sirachai; Chuangcharoendee, Metavee; Pierce, Simon J.; Holmberg, Jason; Araujo, Gonzalo
Abstract: The whale shark Rhincodon typus is a broadly distributed and highly mobile planktivorous shark species. The sharks form predictable aggregations in many areas, providing the opportunity for cost‐effective scientific monitoring through divers and other marine resource users. Sightings of individuals outside of these aggregate zones elsewhere in their range are typically rare. We used a citizen science‐based approach to shed light on occurrence and seasonality in the waters around Koh Tao, Thailand and neighbouring islands in the Gulf of Thailand. Although there is a paucity of quantitative data, anecdotal reports suggest substantial declines in sightings in the early 2000s. We identified a total of 178 individual whale sharks (from 249 sightings) between 2004 and 2019, with most of these (84%) from the 2015–2019 time period due to an increase in sighting reports facilitated by social media and direct marketing. Size estimates were reported for 102 of the sightings, with a range of 2–6 m and mean of 3.7 m overall. Sex was reported for 27% of sightings, with a 2:1 female‐to‐male ratio. Modified maximum likelihood methods suggest whale sharks are transient to Koh Tao and surrounding areas, with whale shark sightings following the regional monsoon cycle. One international resighting was obtained from Malaysian waters (~700 km away). Encouraging citizen science participation is particularly useful in data‐poor regions like the Gulf of Thailand, despite limitations in size and sex estimation reliability, which can play an important complementary role in dedicated research programs.